Reading (Thành phố Hồ Chí Minh, 2010)
LingualForum Hooked on TOEFL Reading( New Edition) is the revised version of Hooked on TOEFL Reading Cram/Crash Course series. It is intended for advanced students preparing for the TOEFL iBT and is based on the most up- to-date information on the test.
Keywords: English language,Tiếng Anh; Examinations,Kỳ thi